An Analysis of 3-Year Outcomes Following Canaloplasty for the Treatment of Open-Angle Glaucoma - Mahmoud A. Khaimi; Justin D. Dvorak; Kai Ding (Journal of Ophthalmology)
Purpose. To report 3-year results investigating the safety and efficacy of canaloplasty for open-angle glaucoma. Setting. University of Oklahoma, Dean McGee Eye Institute, Oklahoma, United States of America. Design. Nonrandomized single-center retrospective chart review. Methods. Adult open-angle glaucoma eyes underwent canaloplasty or combined cataract-canaloplasty surgery. A tensioning suture was placed into Schlemm’s canal in all eyes. Primary endpoints included the mean IOP and mean number of glaucoma medications at each follow-up visit. Secondary endpoints included visual acuity and surgical/postsurgical complications. Results. The study cohort included 277 eyes (mean age, 72.8 years). Overall, the mean baseline IOP of 19.7 mmHg was reduced to 14.3 mmHg,14.0 mmHg, and 15.2 mmHg at 1, 2, and 3 years, respectively (p<0.001). The average medicine use was reduced from 2.1 preoperatively to 0.4 at 12 months, and 0.5 and 0.6 at two and three years, respectively (p<0.001). The frequency of surgical and postsurgical complications was low with no serious adverse events recorded. Conclusion. Canaloplasty was safe and effective in achieving long-term IOP reductions and reduced dependence on antiglaucoma medications.